DESIGNING ICT COMPETENCES-INTEGRATED LANGUAGE AWARENESS (ENGLISH PHONETICS AND PHONOLOGY, ENGLISH MORPHOLOGY AND SYNTAX, AND ENGLISH SOCIOPRAGMATIC) ASSESSMENT INSTRUMENTS FOR ELESP - Tampubolon, Trihartina; Darmahusni (IJLECR (International Journal of Language Education and Cultural Review), 2019)
Abstract The purpose of this research was to design ICT competences-integrated Language Awareness (English Phonetics and Phonology, English Morphology and Syntax, and English Socio-pragmatic) assessment instruments for English Language Education Study Program (ELESP). The Design and Development Research (DDR) acommodatesthis research to produce the models and principles guided by the design, development, and evaluation processes. The data of this research are final test of assessment instruments from five Universities existing assessment instruments of English Language Education Study Program, UNESCO document, European Profiling Grid (EPG) document, and Common European Framework of Reference (CEFR). The reseacher conducts three phases: need analysis, where the writeranalyses the existing assessment instruments of five universities and compare them to ICT competences of EPG, information gathering, and prototypical design. The findings shows the ICT competences of five universities on Technology Literacy of UNESCO. The research results are the procedures to design Table of Specification (ToS), the design ICT competences-integrated in Table of Specification, and design ICT competences-integrated in test and non-test of Language Awareness assessment instruments. Keywords: Assessment instruments, ICT competences, Table of Specification, andLanguage Awareness.